The effects of riboflavin on ischemia/reperfusion induced renal injury: Role on caspase-3 expression - ERTAŞ, BÜŞRA; ÖZBEYLİ, DİLEK; ERCAN, FERİHA; ŞENER, GÖKSEL; ŞENER, TARIK EMRE (MARMARA UNIV, 2019)
Reactive oxygen metabolites play important roles in ischemia/reperfusion (I/R) injury in several organ systems. Riboflavin has been shown to exert antioxidant and/or anti-inflammatory activities in several experimental models. The aim of this study was to investigate the role of riboflavin against I/R injury in the rat kidney. Wistar albino rats 200-300 g weighing were divided into 3 groups. One week after unilateral nephrectomy, the IR procedure was applied to the rats. To induce I/R injury renal pedicle was clamped for 45 minutes and then rats were allowed reperfusion for 6 hours. Riboflavin (25 mg/ kg, orally) or vehicle was administered for one week as pretreatment. After decapitation, kidney tissue samples were taken for the evaluation of malondialdehyde (MDA), an end product of lipid peroxidation; glutathione (GSH), a key antioxidant; and 8-hydroxydeoxyguanosine (8-OHdG), a specific marker of oxidative DNA damage. Furthermore, myeloperoxidase (MPO) and caspase-3 activities were also examined together with histological analysis. Ischemia/reperfusion induced significant increases in MDA and 8-OHdG levels and MPO and caspase- 3 activities, and decrese in GSH levels. In the riboflavin treatment these indices were found to be reversed back to control levels. The present data demonstrated that riboflavin, through its antioxidant effect, attenuates I/R induced acute renal injury in rats.
Keywords: Antioxidants; ischemia reperfusion; riboflavin; caspase; ABDOMINAL AORTIC-ANEURYSM; VITAMIN B-2; OXIDATIVE STRESS; RAT; REPERFUSION; ISCHEMIA; MELATONIN; MYELOPEROXIDASE